Method for Indirect Quantification of CH4 Production via H2O Production Using Hydrogenotrophic Methanogens - Taubner, Ruth-Sophie; Rittmann, Simon K.-M. R. (Frontiers in Microbiology, 2016)
Hydrogenotrophic methanogens are an intriguing group of microorganisms from the domain Archaea. Methanogens exhibit extraordinary ecological, biochemical, and physiological characteristics and possess a huge biotechnological potential. Yet, the only possibility to assess the methane (CH4) production potential of hydrogenotrophic methanogens is to apply gas chromatographic quantification of CH4. In order to be able to effectively screen pure cultures of hydrogenotrophic methanogens regarding their CH4 production potential we developed a novel method for indirect quantification of the volumetric CH4 production rate by measuring the volumetric water production rate. This method was established in serum bottles for cultivation of methanogens in closed batch cultivation mode. Water production was estimated by determining the difference in mass increase in a quasi-isobaric setting. This novel CH4 quantification method is an accurate and precise analytical technique, which can be used to rapidly screen pure cultures of methanogens regarding their volumetric CH4 evolution rate. It is a cost effective alternative determining CH4 production of methanogens over CH4 quantification by using gas chromatography, especially if applied as a high throughput quantification method. Eventually, the method can be universally applied for quantification of CH4 production from psychrophilic, thermophilic and hyperthermophilic hydrogenotrophic methanogens.